1998
DOI: 10.1097/00006534-199803000-00029
|View full text |Cite
|
Sign up to set email alerts
|

Improved Free Musculocutaneous Flap Survival with Induction of Heat Shock Protein

Abstract: The cellular response to a wide variety of stresses results in the synthesis of a family of stress response proteins termed heat shock proteins. Recent studies have demonstrated that heat shock proteins produced in response to an initial stress seem to protect against subsequent unrelated stresses. Importantly, hyperthermia-induced heat shock proteins provided protection from ischemia/reperfusion injury in several organ transplantation models. We hypothesized that free musculocutaneous flap survival could be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 22 publications
1
15
0
1
Order By: Relevance
“…[1][2][3][4][5][6] The IPC phenomenon was first described in heart by Murry et al 2 Similar results were reported for other organ systems, for example liver 23 and kidney. 24 Various factors such as heat-shock proteins, 25,26 adenosine, 27,28 cyclooxygenase, 29 bradykinin, 30 and endogenous opioid system 3 seem to be involved in the IPC mechanism. NO, 28,31,32 ATP-sensitive K ϩ channels, 22,[33][34][35]15 are probably the more emphasized players in the scenario.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The IPC phenomenon was first described in heart by Murry et al 2 Similar results were reported for other organ systems, for example liver 23 and kidney. 24 Various factors such as heat-shock proteins, 25,26 adenosine, 27,28 cyclooxygenase, 29 bradykinin, 30 and endogenous opioid system 3 seem to be involved in the IPC mechanism. NO, 28,31,32 ATP-sensitive K ϩ channels, 22,[33][34][35]15 are probably the more emphasized players in the scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Eine positive Korrelation mit dem Überleben von Lappenplastiken konnte ebenso für die Expression von Hitze-Schock-Proteinen, sog. "heat-shock proteins" (HSPs), beobachtet werden, die bei der hyperthermischen Präkonditionierung von Lappenplastiken induziert wird [62]. Für HSP72 beispielsweise konnte eine Inhibition von Apoptose nachgewiesen werden [7].…”
Section: Mikrochirurgische Lappenplastikenunclassified
“…There have also been several studies on HSP72 induction relating to the ischemic condition of various organs including the skeletal muscle [7,16] and skin [17,31] that are among the ischemic organs in ischemia of the lower leg.…”
Section: Introductionmentioning
confidence: 99%